Confirmatory Factor Analysis of Perceived Educational Effectiveness Scale for Heads of Institutions of Students with Hearing Impairment - Zafar, Saira; Fazil, Hina (Annals of Human and Social Sciences, 2022)
The aim of this study was to create a native scale that would assess the perception of the heads of institutions for students with hearing impairment working in Government special education institutes of Punjab Province regarding the educational effectiveness as well as the psychometric properties of the scale’s effectiveness of educational services for those heads of institutions. This study was carried out using a quantitative paradigm. The population of this study was the heads of Government special education institutions for students with hearing impairment in Punjab Province. For this investigation, the sample was chosen using a random sampling strategy. As a sample for this study, 55 heads of institutions were chosen. The researchers produced an indigenous scale. The five-point Likert scale was used to evaluate each statement. 49 statements were used to evaluate perceived educational effectiveness. Confirmatory factor analysis was carried out through IBM SPSS AMOS (Analysis of moment structure) version 25.0 using structural equation modeling (SEM).